2018
DOI: 10.3390/rs10030421
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ability of Spectral Indices of Hydrocarbons and Seawater for Identifying Oil Slicks Utilizing Hyperspectral Images

Abstract: Abstract:It is important to detect floating oil slicks after spill accidents, and hyperspectral remote sensing technology is capable of achieving this task. Traditional methods mainly utilize the spectral indices of hydrocarbons to detect floating oil slicks, but are poor at distinguishing the thickness of oil slicks and cannot detect sheens. Since the spectra of oil slicks should be affected by seawater as well as oil, this paper investigated the use of spectral indices of hydrocarbons and seawater to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Hence, it is possible to combine information in the separate wavelength bands in order to detect oil spills [26]. In [27], it is shown that it is possible to differentiate between water, oil slicks, and interference, such as algae. In [28] a solution is presented for automated detection while using object detection based on RGB cameras mounted on a UAV.…”
Section: Literaturementioning
confidence: 99%
“…Hence, it is possible to combine information in the separate wavelength bands in order to detect oil spills [26]. In [27], it is shown that it is possible to differentiate between water, oil slicks, and interference, such as algae. In [28] a solution is presented for automated detection while using object detection based on RGB cameras mounted on a UAV.…”
Section: Literaturementioning
confidence: 99%
“…A series of parameters were used to train the model using the training samples. The 3-fold cross-validation was used to the training samples [35], which helped select the best combination of parameters. Each of the selected methods was tested using the test samples to calculate the accuracy.…”
Section: Overall Proceduresmentioning
confidence: 99%
“…An oil spill accident results in the rapid leakage of a large amount of oil. Oil slicks caused by accidents float to the surface of the sea, wreaking havoc on the marine environment (Zhao et al, 2018). Some oil pollution is caused not by ship collisions, but by routine ship operations such as tank cleaning and engine effluent discharges.…”
Section: Introductionmentioning
confidence: 99%